MODEL EVALUASI KIRIKPATRICK DAN APLIKASINYA DALAM PELAKSANAAN PELATIHAN (LEVEL REAKSI DAN PEMBELAJARAN) DI PUSAT PENDIDIKAN DAN PELATIHAN PERUM JAKARTA - Aminah, Hania (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2015)
MODEL EVALUASI KIRIKPATRICK DAN APLIKASINYA DALAM PELAKSANAAN PELATIHAN (LEVEL REAKSI DAN PEMBELAJARAN) DI PUSAT PENDIDIKAN DAN PELATIHAN PERUM JAKARTA Hania Aminah Fakultas Ekonomi, Universitas Negeri Jakarta Email: haniaaminah@gmail.com ABSTRACT In order to avoid the inefficiency of the training, the training should be measured. The research aim to determine the effectiveness of information and training through the implementation of the evaluation model is to implement two levels which consist of reactions and learning levels, using Kirkpatrick’s model. This research was conducted at the Learning and Training Center of Central Jakarta, with a sample of all participants of training. Data collection using a questionnaire that has been tested by using content validity, whereas tests use SPSS. The results showed that the reaction of trainees are satisfied with the implementation of the training that was conducted and the results are good and improving learning are assessed from the pre-test and post-test. The resulting increase in the difference was significant, but when viewed from the aspect of knowledge, understanding and application, the result of the difference increased, but not significantly. Keywords: Training, Evaluation, Kirkpatrick Model, Employees